Identification of a Natural Source of Resistance to Watermelon Chlorotic Stunt Virus in an Indigenous Accession of Cucumis Melo Var. Agrestis - T. Yousif, Mohamed; A. Dafalla, Gasim; E. El Jack, Ali (المجلة الزراعية, 2021)
Watermelon chlorotic stunt virus (WCSV) is among the most important viral diseases of the family Cucurbitaceae . It is a bipartite begomovirus (DNA-A and DNA-B genome components) that belongs to the family Geminividae (Walkely et al., 1990). It causes severe crop losses, particularly in watermelon and melon (Lecoq et al., 1994). In Sudan, WCSV causes high reduction in yield and quality of watermelon, melon, snake cucumber and squashes. Leaves of infected plants are crinkled, stunted and develop striking chlorotic mottle. The whole plant looked stunted and chlorotic and may be devoid of marketable fruits (Walkely et al ., 1990). Resistance to major diseases is very common among indigenous Sudanese melons, Tibish and agrestis (C. melo var. agrestis) , compared to other melon types (Mohamed, 2000).    Experiments were conducted at the University of Gezira Research Farm in April (1996-1997) to identify a natural source of resistance to watermelon chlorotic stunt virus in Cucumis melo L. The screened material included: 101 accessions of C. melo var. cantalupensis and C. melo var flexuousus collected in Sudan; nine accessions belong to the indigenous Humaid type (C. melo var. agrestis ) and eleven introduced lines such as P1 313970, P1 131375, Pl 255478, Vedrantais, Nantais Oblong, MR-I, Isoblon, Virgos, Margot and Zumo. The inoculation pressure of the virus in the field was increased by growing plants of the susceptible watermelon cultivar "Sugar Baby", obtained from Peto Seed Company, about one month before conducting the screening experiments.